Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1073191118791042
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of the Trauma Symptom Checklist–40 Total and Subscale Scores

Abstract: The Trauma Symptom Checklist-40 (TSC-40) is commonly used in clinical research to index history of childhood maltreatment and assess complex trauma symptomatology in adults. Yet the dimensional structure of this measure has not been examined. We examined the factor structure of the TSC-40 in a sample of 706 undergraduate students, measurement invariance of the TSC-40 across groups with or without a history of abuse-related and multiple trauma, and the association between the TSC-40 and other trauma indices. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Studies are presented in the order they appear in the text. FY = fiscal year; ICD-9-CM = International Classification of Diseases 9 Clinical Modification; MST = military sexual trauma; VA = Veterans Administration; ICD-9 = International Classification of Diseases; TSI-2 = Trauma Symptom Inventory-2; CSA = childhood sexual abuse; PTSD = post-traumatic stress disorder; CAPS = Clinician Administered PTSD Scale; TSC-40 = Trauma Symptom Checklist-40; DSM-5 = Diagnostic and Statistical Manual of Mental Disorders ; DDRI-2 = Deployment Risk and Resilience Inventory-2; SES = Sexual Experiences Survey; CHIPS = Cohen-Hoberman Inventory of Physical Symptoms; FSFI = Female Sexual Function Index; SSS-W = Sexual Satisfaction Scale for Women. a Elliott and Briere (1992), Rizeq, Flora, and MCann (2018), and Whiffen and Benazon (1997). …”
Section: Methodsmentioning
confidence: 99%
“…Studies are presented in the order they appear in the text. FY = fiscal year; ICD-9-CM = International Classification of Diseases 9 Clinical Modification; MST = military sexual trauma; VA = Veterans Administration; ICD-9 = International Classification of Diseases; TSI-2 = Trauma Symptom Inventory-2; CSA = childhood sexual abuse; PTSD = post-traumatic stress disorder; CAPS = Clinician Administered PTSD Scale; TSC-40 = Trauma Symptom Checklist-40; DSM-5 = Diagnostic and Statistical Manual of Mental Disorders ; DDRI-2 = Deployment Risk and Resilience Inventory-2; SES = Sexual Experiences Survey; CHIPS = Cohen-Hoberman Inventory of Physical Symptoms; FSFI = Female Sexual Function Index; SSS-W = Sexual Satisfaction Scale for Women. a Elliott and Briere (1992), Rizeq, Flora, and MCann (2018), and Whiffen and Benazon (1997). …”
Section: Methodsmentioning
confidence: 99%
“…CTS-S has been used with a variety of clinical and community samples of adults and adolescents from numerous sociocultural groups and has been shown to possess adequate reliability (with an alpha ranging between .80 and .92), good construct validity (e.g., , Kira, Lewandowski, Somers, Yoon, & Chiodo, 2012Kira, Smith, Lewandowski, & Templin, 2010), and validity across different cultural and clinical groups, including American Indians, Mayans, Palestinians, Egyptians, refugees, and torture survivors from 32 countries (e.g., Kira, Ashby, Odenat, & Lewandowski, 2013;Kira, Barger et al, 2019, 2020Kira, Fawzi et al, 2013;Kira, Omidy, & Ashby, 2014;Kira et al, 2010). The measure has been used in several studies as a comprehensive measure of stress and trauma (e.g., Bedoya et al, 2020;Eltan, 2019;Gillespie & Gates, 2013;Head, Singh, & Bugg, 2012;Lee, & Lee, 2018;Millender, 2013;Omidy, 2012;Rizeq, Flora, & McCann, 2018;Robles et al, 2009), and has been found to have good reliability and predictive validity. It has been translated into different languages, including Arabic, Spanish, Polish, Korean, Turkish, and Nigerian, and proved to have good psychometric properties in these languages.…”
Section: Description Of the Measurementioning
confidence: 99%
“…Furthermore, TSC-40 has indicated predictive validity with reference to child sexual abuse in clinical and nonclinical samples (Neal & Nagle, 2013). Furthermore, a recent examination of the factor structure of TSC-40 found a strong invariance across groups with or without histories of abuse and trauma, providing support for its factor structure (Rizeq et al, 2018).…”
Section: Methodsmentioning
confidence: 95%